Efektivitas Penanaman Nilai Agama untuk Membentuk Persepsi Orang Tua di RA Darul Ulum - Endang Ratnasari; Titin Faridatun Nisa'; Yulias Wulani Fajar (Universitas Trunojoyo Madura, 2017)
Applying religion value is one of the more dominating learning in RA (Raudhatul Athfal) Darul Ulum. The applying of religion values include learning of Qur'an and Al Hadith also Islamic Education. Based on the parent’s observations, the applying religion values can be the interest point to form parent’sperception. This study aimmed to investigate the implementation, activities, results, and the parent’s perception of applying religious values in groups A1 and A2 RA Darul Ulum to form the parent’s perception. The research sample of this study are 33 parents. The writer uses quantitative approach. The techniques of data collection are questionnaires, observations, interviews, and documentations. This study uses data analysis techniques of statistics descriptive and hypothesis test by using t test of right side. The results of the data analysis of applying religion value can be known that the percentage of applying religion values is 96%, the activity percentage of applying religion values is 75%, the result percentage of applying religion values is 68%, and the perception percentage of applying religion values is 82%. Based on the percentage results can be inferred that applying religion value in RA Darul Ulum is very effective to form parent’s perception.